The Effectiveness Test Of Aromatherapy Candles Made From Ciplukan (Physalis Angulata L.) Leaf Extract Against Aedes Aegypti Mosquitoes - Weni Mulyani; Titi Lasmini; Mutia Rani (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Dengue Hemorrhagic Fever (DHF) is a disease caused by a virus transmitted through the bite of mosquitoes, particularly the Aedes aegypti species. The use of natural insecticides is considered the safest method of control as it has minimal side effects. One of the natural insecticides that can be utilized to control DHF vectors is an insecticide rich in secondary metabolites, such as morel berry (Physalis angulata L.) leaves. The aim of this study was to determine the effectiveness of aromatherapy candles made from morel berry leaf extract (Physalis angulata L.) against Aedes aegypti mosquitoes. This research was a quasi-experimental study with simple random sampling. The study consisted of four test groups: aromatherapy candles containing morel berry leaf extract at doses of 200 mg, 300 mg, and 400 mg, as well as a negative control group. Observations were made over a 120-minute period. The mortality rate of Aedes aegypti mosquitoes after treatment was assessed through two tests: one conducted immediately and the other after three days of storage. In the immediate test, the mosquito mortality rate was 30% at 200 mg, 40% at 300 mg, and 60% at 400 mg. In the test after three days of storage, the mortality rate was 20% at 200 mg, 30% at 300 mg, and 80% at 400 mg. It can be concluded that aromatherapy candles made from morel berry leaf extract (Physalis angulata L.) are effective and stable in killing Aedes aegypti mosquitoes.